Accession Poland's to the EU: Some lessons from international trade theory - Elçzbieta Czarny; Günter Lang (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
The Eastern enlargement of the European Union is significantly increasing the area, where free trade of goods and services are among the core principles of all member countries. Existing economic borders between the applicant countries and the current EU members will have to be broken down, leaving no room for the protection of non-viable industries. In this paper, we apply traditional as well as new theories of international trade in order to identify sectors of the Polish economy with a comparative (dis)advantage. As a main result, human capital- as well as capital-intensive industries will be among the prominent losers of Poland's accession to the EU. This structural change will be accompanied by significant changes in the income distribution. In the long-run, inter-industry trade will be substituted by intra-industry trade. However, because of a high number of determinants, relatively little can be said about the industries which will successfully participate in intra-industry trade.
urn:nbn:de:bvb:384-opus4-712457
Keywords: F1; 330; EU Eastern Enlargement; International Trade Theory; Intra-industry Trade